2014
DOI: 10.1063/1.4892475
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of photothermal conversion on the photo-induced deformation of amorphous carbon nitride films prepared by reactive sputtering

Abstract: The photo-induced deformation of hydrogen-free amorphous carbon nitride (a-CNx) films was investigated under visible-light illumination. The films gave rise to photothermal conversion by irradiation. In this study, we investigated the effects of thermal energy generated by irradiation on the deformation of a-CNx/ultrathin substrate bimorph specimens. The films were prepared on both ultrathin Si and SiO2 substrates by reactive radio-frequency magnetron sputtering from a graphite target in the presence of pure n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Therefore, it is reasonable to surmise that the occurrence of δ t was caused mainly by light. In the case of using the Si substrate, the surface temperature change of the a-CN x films was almost zero because of the higher thermal diffusivity, but the change of δ t was almost similar to the case of SiO 2 substrates [10].…”
Section: B Photomechanical Response Of A-cnx Filmsmentioning
confidence: 87%
See 3 more Smart Citations
“…Therefore, it is reasonable to surmise that the occurrence of δ t was caused mainly by light. In the case of using the Si substrate, the surface temperature change of the a-CN x films was almost zero because of the higher thermal diffusivity, but the change of δ t was almost similar to the case of SiO 2 substrates [10].…”
Section: B Photomechanical Response Of A-cnx Filmsmentioning
confidence: 87%
“…The maximum value of δ t was obtained by the specimen deposited at 573 K when the incident light was turned on. Although the reason for the maximum value of δ t observed in the a-CN x films deposited at 573 K has not been elucidated yet, we think that the existence of the C≡N triple bonds is necessary for the displacement and, in particular, the structures with the high A i /A n ratio and relatively small graphite cluster size play an important role for the displacement [9,10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amorphous carbon nitride (a-CN x ) thin films have attracted considerable attention owing to their unique properties, such as high wear resistivity 1 , low friction coefficient 2 , 3 , variable optical bandgap 4 , environment-dependent electrical resistance 5 , and biocompatibility 6 , 7 . Most recently, it was found that a-CN x films exhibit photomechanical response 8 , 9 . This response manifests as temporal deformation under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%